Zadania gmin z zakresu zaopatrzenia w wodę i odprowadzanie ścieków - Kotlińska, Janina (The Responsibilities of Municipalities as Regards Water Supply and Sewage Disposal, 2007)
Rendering services such as collective water supply and sewage disposal is one of the obligatory duties of municipalities in Poland. Those services can be provided both by budgetary units and commercial companies. These companies collect fees for rendering water supply and disposal services. Their volume depends on the costs of usage of the existing water supply and disposal system, expenditure on the development of the new element of infrastructure as well as future profit of the company. It is thus, not surprising that these fees differ on the territory of the whole country very much.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 340-349